Livelihood Strategies of Marginalized Women Street Vendors: An Intersectional Study from Machhapokhari, Kathmandu - Adhikari, Sanjita; Khatri, Guman Singh; Poudel, Kabita (Journal of Multidisciplinary Research Advancements, 2026)
Street vending under the metropolitan restrictions in Kathmandu has been more regulated especially since 2022. Previous studies have illuminated the financial contributions and the difficulties faced by vendors. But little attention has been given to the livelihood strategies of women vendors through an intersectional lens. This study focuses on Machhapokhari, one of the busiest transit hub areas where women vendors are highly visible. This study draws on qualitative methods including participants’ observations and in-depth interviews with 21 women vendors across multiple categories based on gender, migration status, class, marital status and age to examine how these interacting factors influence survival strategies. The finding indicates that women street vendors rely on an informal network for entry, guidance and support. As well as adopt useful decision-making tactics for what to sell, where to set up for vending and how to juggle multiple tasks to thrive in a city that can be harsh and unwelcoming. These strategies depict that it’s both a strength and a part of resilience and expose compound vulnerabilities faced by single mothers with age and migrant women without husband support, kinship backing. By understanding each individual's surreal experiences through intersectionality. The study contributes on intersectional sociology and feminist urban studies by promoting inclusive urban government that acknowledges vendors as essential to the social and economic fabric of the city.